2016
DOI: 10.1116/1.4947120
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition synthesized TiOx thin films and their application as microbolometer active materials

Abstract: Low-temperature atomic layer deposition of TiO 2 thin layers for the processing of memristive devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…10), and pure TiO 2 thin films grown at 200 C have the maximum TCR of À2.5%/K (Ref. 14) in the temperature range of the current work, which are considerably less than that of the TZO films proposed in this study. ZnO, when deposited at 200 C, was shown to have a resistivity of 0.015 X cm, 24 which makes it behave like a very highly doped (unintentional) semiconductor, thereby having low TCR values.…”
Section: A Electrical Characterization Of Tzo Thermistorscontrasting
confidence: 51%
“…10), and pure TiO 2 thin films grown at 200 C have the maximum TCR of À2.5%/K (Ref. 14) in the temperature range of the current work, which are considerably less than that of the TZO films proposed in this study. ZnO, when deposited at 200 C, was shown to have a resistivity of 0.015 X cm, 24 which makes it behave like a very highly doped (unintentional) semiconductor, thereby having low TCR values.…”
Section: A Electrical Characterization Of Tzo Thermistorscontrasting
confidence: 51%
“…At present, there are few ways to characterize TiO 2−x films by TCR, which are mainly formed by RF reactive magnetron sputtering and DC sputtering deposition [26]. Kwon et al [29] studied reactive sputtering TiO 2−x thin films and obtained TCR values up to 2.8 -%/K Reddy et al [8,23] grew TiO 2−x films under the same deposition technique but different oxygen content, the TCR value was 3.66 −%/K Jiang et al reported the TCR of TiO 2−x thin film prepared by reactive DC sputtering method was 3.3 −%/K [50].…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…The Nb-doped TiO 2−x films showed a controllable resistivity, low 1/f noise parameter for 10 -12 , and relatively high TCR value for 3.1 -%/K [25]. Tanrikulu et al [26] synthesized the TiO 2−x thin films by atomic layer deposition grown at 150 °C and annealed at 300 °C, which has a very high TCR for 9 -%/K Ju et al [27,28] fabricated amorphous TiO 2−x thin films at room temperature by controlling the substrate temperature and oxygen partial pressure, the films' electrical properties could be adjusted with the O/Ti ratio changed from 1.73 to 1.97, and the TCR of the samples also varied from 1.2 to 2.3 -%/K. Based on material research, Kwon et al [29] reported the first TiO 2−x films based 50 μm pitch microbolometer with the NETD of 34 mK.…”
Section: Introductionmentioning
confidence: 97%
“…Si 1-x Sn x alloys of compositions within the range of our samples are shown to adequately follow Vegard's law, [1][2][3] which, for our samples, reads as follows…”
Section: Bandgap Estimations For Si 1-x Sn X Alloysmentioning
confidence: 99%
“…This active temperature sensing layer converts the change in temperature induced by the absorbed infrared radiation into a change in electrical resistance, which is then converted to an electrical signal and digitized by the complementary metaloxide-semiconductor (CMOS) read-out integrated circuit (ROIC) and, finally, translated into an image. [1,2] A successful thermistor material ought to possess a high TCR, moderate resistivity for CMOS ROIC impedance matching, low 1/f noise, and, preferably, CMOS process compatibility. [3] The most important property of the bolometric thermometer thin film is TCR.…”
Section: Introductionmentioning
confidence: 99%